Prevalence of intestinal parasites in a cohort of HIV-infected patients from Antioquia, Colombia (2021)
ABSTRACT: Introduction: HIV infection is still a public health problem worldwide and co-infections with other infectious agents including intestinal parasites are of particular concern, mainly in developing countries like Colombia. Objective: To conduct a cross-sectional study in patients attending an HIV care program in Antioquia given that there have been few intestinal parasites prevalence studies among the HIV population in the country. Material and methods: We evaluated stool samples from 192 patients by direct wet mount and concentration, modified Ziehl Neelsen staining, and agar plate culture. Univariate and correlation analyses were done to explore the association between socio-demographic and clinical characteristics and parasitological data. Results: The overall prevalence of intestinal parasites in HIV-positive subjects was 29.2% (56/192; 95% CI: 22.8% - 35.6%). Entamoeba histolytica/dispar/moshkosvkii with 13.0% (25/192; 95% CI: 8.2% - 17.8%) and Blastocystis with 12.0% (23/192; 95% CI: 7.4% - 16.6%) were the most frequent. Opportunistic parasites like Cryptosporidium spp. and Cystoisospora belli were less prevalent, each one with 0.5% of positive samples (1/192; 95% CI: 0.1% - 1.5%). Commensal protozoa were also detected with a prevalence of 18.8% (36/192; 95% CI: 13.3% - 24.3%). Most of the individuals in the study had a controlled viral load and an LTCD4 count greater than 200 cel/μL. A small percentage (9.3%) had diarrhea. Bivariate analysis and multivariate logistic regression showed that only age and having pets had a significant association with intestinal parasites in this cohort. Conclusions: Our results confirmed that the evaluated population is at high risk of intestinal parasite infection, which highlights the need for routine screening of gastrointestinal parasites to provide prompt treatment and reduce possible complications.